1988
DOI: 10.1176/appi.psychotherapy.1988.42.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Group Therapy in Manic-Depressive Illness

Abstract: Noting the recent growth of self-help groups for manic-depressive illness and considering the scarcity of empirical studies on the effectiveness of group therapy in the treatment of this illness, this review examines the three available reports on groups and adds a fourth report on the authors' experience with a group over four-and-a-half years. The evidence argues in favor of combined lithium and group therapy. Some research questions and strategies for investigation follow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…67 An additional study 60 reported that hospitalization time decreased from 16.8 to 3.6 weeks. The other seven studies [62][63][64][65][66][70][71][72] suggested psychosocial benefits without documenting reduced morbidity or time-inhospital. Adherence to group therapy also varied, with high attendance rates (80%, 87%) in at least two studies 58,59 but a drop-out rate of 55% in another.…”
Section: Group Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…67 An additional study 60 reported that hospitalization time decreased from 16.8 to 3.6 weeks. The other seven studies [62][63][64][65][66][70][71][72] suggested psychosocial benefits without documenting reduced morbidity or time-inhospital. Adherence to group therapy also varied, with high attendance rates (80%, 87%) in at least two studies 58,59 but a drop-out rate of 55% in another.…”
Section: Group Therapymentioning
confidence: 99%
“…Adherence to group therapy also varied, with high attendance rates (80%, 87%) in at least two studies 58,59 but a drop-out rate of 55% in another. 63 In addition to reduced hospitalization, benefits reported with group therapy included increased adherence to prescribed medication [65][66][67] and improved economic status 60,61 or vocational and social functioning. 68,70 Only one study 68 found evidence of fewer and less severe episodes of mania or depression over a year of follow-up.…”
Section: Group Therapymentioning
confidence: 99%
“…Illness effects in social adjustment and interpersonal aspects of coping with the illness would be especially interesting for inclusion in a therapy group [17]. Other authors [18] suggest starting group therapy during hospitalization, even when in an acute phase.…”
Section: Group Therapymentioning
confidence: 99%
“…Four other studies have longer follow-ups (5 to 12 years). However, the differences between the additional group treatment periods and follow-ups arenot clear (Knpke and Robinson, 1985;Wulsin et al, 1988;Waard de, 1990;…”
Section: Introductionmentioning
confidence: 99%